Enabling optimization of complex distillation configurations in GAMS with CAPE-OPEN thermodynamic models. (January 2022) - Krone, David; Esche, Erik; Asprion, Norbert; Skiborowski, Mirko; Repke, Jens-Uwe
Abstract: Optimization of complex process models, e.g., those, resulting from conceptual design of distillation processes, with optimization environments such as GAMS, AMPL, or AIMMS is still thwarted by the manual implementation necessary for the interface to external thermo engines. In this contribution, we address this issue by automatically generating all code for interfacing GAMS with an external CAPE-OPEN thermodynamic property package. The distillation models in our approach are assembled in a modular way by combining multiple general vapor-liquid equilibrium stage models. A method, where all existing vapor-liquid-equilibria are relaxed is proposed and examined for enhanced model stability. The ability of our optimization approach is shown by the results of two examples that determine an optimum energy-targeted design of a fully thermally coupled dividing wall column for the separation of a zeotropic mixture of n -pentane, n -hexane, and n -heptane and an azeotropic mixture of acetone, methanol, and water.